A Study on Impact of Social Media as a Tool for Revenue Generation for Various F (Global Journal of Management and Business Research, 2022)
In this era of digitalisation, customers have all access to the information of hotel through various communication channels.Using these different communication or digital channels hotels are generating revenue from different sources.Social media has become a new way for communicating, supporting hotels and restaurants in recognizing customer#x2019;s needs and wants. According to the findings, social media has a significant influence on the restaurant industry. Restaurants that accept social media see an increase in sales and client flow. Restaurants make use of social media channels like Facebook and Instagram. Thus, the present study focuses on how social media has helped hotel to generate revenue for various food outlets at Hotel Crowne Plaza, Greater Noida.
Keywords: digitalization; communication channels; revenue; recognizing